Solar Powered Irrigation System Design with Venturimeter for Utilizing Natural Resources - Vivek Viswanadha; P.H.J. Venkatesh; Sura Srinivasa Rao (International Journal of Energy and Thermal Applications, 2023)
This research focuses on enhancing crop productivity in agriculture by ensuring high quality and quantity of crops. Crops needs to be given adequate nutrients in an efficient and timely fashion as a way to accomplish this.. Thus, liquid-based fertilizers are selected for this purpose. However, farmers often face challenges in supplying fertilizers with the required quantity and precision. To address this issue, we propose a solution that leverages solar energy to power a submersible pump, enabling the supply of stored rainwater and liquid fertilizer to each plant. To ensure a uniform rate of flow for both the liquid fertilizer and water, we design a venturimeter throat diameter optimized for strawberry plantations. This approach aims to minimize effort and optimize the utilization of natural resources such as rainwater and solar energy for sustainable and effective agriculture practices.
Keywords: Solar Energy; Submersible pump; and sustainable agriculture; strawberry plantation; uniform rate of flow; venturimeter throat diameter